Empowering Digital Technologies: Students' Literacy Ability - Kartika Kartika; Triarko Nurlambang (Universitas Muhammadiyah Semarang, 2022)
The ability of literacy and numeracy in this digital era is indispensable in increasing global competitiveness. Digital literacy with critical thinking and higher thinking makes students' ability to understand science and numeracy concepts better. Digital literacy capabilities carried out with a national assessment carried out in 2021 will become a reference for teachers later to be able to teach students better digital literacy skills and technology. This research was conducted using a descriptive method through literature review and data on student literacy scores at the high school level in Jakarta when the Ministry of Education and Culture 2022 national assessment was carried out. The literacy skills of students who were still lacking, especially because they were not familiar with presenting questions with various forms of questions, had to be introduced to the concept of good reading, so that the students are not misunderstandings the context of questions for empowering digital literacy and technology